위상수학적 데이터 분석법을 이용한 수학학습 불안 분석 사례 - 고호경; 박선정 (East Asian Mathematical Journal, 2018)
Recently, Topological Data Analysis (TDA) has attracted attention among various techniques for analyzing big data. Mapper algorithm, which is one of TDA techniques, is used to visualize the cluster diagram. In this study, students were clustered according to the characteristics and degree of mathematics anxiety using a mapper, and students were visualized according to mathematics anxiety. In order to do this, Mathematical Anxiety Scale (Ko & Yi, 2011) in the aspect of mathematical instability in terms of teaching - learning, ie, Nature of Mathematics, Learning Strategy, Test/Performance is used. And the number of questions that measure the anxiety of mathematics can be extracted by extracting the most relevant items among the items that measure the anxiety of mathematics.
Keywords: Topological Data Analysis; Big data analysis; Affective domain